Patient-reported outcomes in patients with a germline BRCA mutation and HER2-negative metastatic breast cancer receiving olaparib versus chemotherapy in the OlympiAD trial. (October 2019) - Robson, Mark; Ruddy, Kathryn J.; IM, Seock-Ah; Senkus, Elżbieta; Xu, Binghe; Domchek, Susan M.; Masuda, Norikazu; Li, Wei; Tung, Nadine; Armstrong, Anne; Delaloge, Suzette; Bannister, Wendy; et al.
Abstract: Background: The phase III OlympiAD study (NCT02000622) showed a statistically significant progression-free survival benefit with olaparib versus chemotherapy treatment of physician's choice (TPC) in patients with a germline BRCA mutation and human epidermal growth factor receptor 2-negative metastatic breast cancer. From this study, we report the effect of olaparib on health-related quality of life (HRQoL). Methods: Patients were randomised 2:1 to olaparib monotherapy (300 mg twice daily) or single-agent TPC. The primary HRQoL end-point was mean change from baseline in the two-item global health status/QoL score determined from patient-completed European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30-item module (EORTC QLQ-C30) questionnaires and assessed using a mixed model for repeated measures. Symptoms and functioning domains, best overall response and time to deterioration of QoL were also evaluated. Results: Overall questionnaire compliance rates were 93.2% for olaparib and 76.3% for TPC. Between-treatment global health status/QoL comparison showed a significant improvement in the olaparib arm versus the TPC arm, with mean change of 3.9 (standard deviation 1.2) versus −3.6 (2.2), a difference of 7.5 points (95% confidence interval [CI]: 2.48, 12.44; P  = 0.0035). A higher proportion of patients in the olaparib arm showed a best overall response of 'improvement' in global health status/QoL (33.7% vs 13.4%). Median time to global health status/QoL deterioration was not reached in olaparib patients and was 15.3 months for TPC patients (hazard ratio: 0.44 [95% CI: 0.25, 0.77]; P  = 0.004). For EORTC QLQ-C30 symptoms and functioning subscales, only nausea/vomiting symptom score was worse in the olaparib arm than in the TPC arm (across all visits compared with baseline). Conclusion: HRQoL was consistently improved for patients treated with olaparib, compared with chemotherapy TPC. Highlights: Quality of life (QoL) during treatment was assessed by EORTC QLQ-C30 questionnaire. There was significant improvement in QoL score for olaparib versus chemotherapy. More patients receiving olaparib showed an improvement in functional subscales. Only nausea/vomiting symptom score was worse with olaparib versus chemotherapy.